Severe achondroplasia due to two de novo variants in the transmembrane domain of FGFR3 on the same allele: A case report. Issue 3 (23rd January 2020) - Nagata, Tadashi; Matsushita, Masaki; Mishima, Kenichi; Kamiya, Yasunari; Kato, Kohji; Toyama, Miho; Ogi, Tomoo; Ishiguro, Naoki; Kitoh, Hiroshi
Abstract: Background: Achondroplasia (ACH), the most common form of short‐limbed skeletal dysplasia, is caused by gain‐of‐function mutations in the fibroblast growth factor receptor 3 ( FGFR3 ) gene. More than 97% of patients result from a heterozygous p.G380R mutation in the FGFR3 gene. We present here a child who had two de novo variants in the FGFR3 on the same allele, a common p.G380R mutation and a novel p.S378N variant. Methods: A 3‐year‐old Japanese girl born from non‐consanguineous healthy parents showed more severe clinical and radiological phenotypes than classic ACH, including severe short‐limbed short stature with marked ossification defects in the metaphysis and epiphysis, hydrocephalus and cervicomedullary compression due to foramen magnum stenosis, prolonged pulmonary hypoplasia, and significant delay in the gross motor development. Genomic DNA was extracted from the proband and whole‐exome sequencing was performed. The variants were subsequently confirmed by Sanger sequencing. Results: Mutation analysis demonstrated that the proband had p.S378N (c.1133G>A) and p.G380R (c.1138G>A) variants in the FGFR3 gene. Both variants were not detected in her parents and therefore considered de novo. An allele‐specific PCR was developed in order to determine whether these mutations were on the same allele (cis) or on different alleles (trans). The c.1138G>A mutation was found in the PCR product generated with the primer for the mutant 1133A, but it was not detected in the product with the wild‐type 1133G, confirming that p.S378N and p.G380R variants were located on the same allele (cis). Conclusion: This is the second case who had two FGFR3 variants in the transmembrane domain on the same allele. The p.S378N variant may provide an additive effect on the activating receptor with the p.G380R mutation and alter the protein function, which could be responsible for the severe phenotype of the present case. Abstract : We present a case who had two de novo variants in the FGFR3 on the same allele, a common p.G380R mutation and a novel p.S378N variant. The p.S378N variant may provide an additive effect on the activating receptor with the p.G380R mutation and alter the protein function, which could be responsible for severe phenotype of the present case.